Genotyping analysis on foodborn Listeria monocytogenes starins isolated in Beijing region - Xiao-hui CHANG; Xiao-nan WAN; Jie ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine genotype distribution of Listeria monocytogenes (Lm) strains isolated from meat product specimens in Beijing and genetic correlations among the strains with whole genome sequencing (WGS). MethodsTotally 110 Lm strains were sequenced with WGS and analyzed with multilocus sequence typing (MLST). Gene assembly, prediction and function annotation for WGS results of the strains were performed using relevant softwares. The Comprehensive Antibiotic Research Database (CARD) and the Virulence Factors Database (VFDB) were used to screen drug resistance genes and pathogenic genes of the isolated Lm strains. ResultsThe 110 Lm strains were classified into 17 sequence type (ST) types; among the 17 ST types, there was a unknown ST type (namely STnew1) and ST9 was the dominant ST type. The STnew1 has multiple drug resistance genes including genes against macrolides, aminoglycosides, oxazolidinones, chloramphenicols, tetracyclines, and trimethoprim and gene deletion of prfA, hpt, plcA, plcB, inlC, and hlyA. Of the 110 Lm strains, all carried the Listeria monocytogenes pathogenicity island (LIPI-1) gene, except for 6 non-pathogenic strains, and 20.9% carried drug resistance genes. ConclusionMultiple drug resistance genes are prevalence in Listeria monocytogenes strains isolated from meat products and LIPI-1 gene is dominant among the drug resistance genes. The results suggest that contamination of Listeria monocytogenes in meat products needs to be monitored and controlled to reduce the risk of foodborne diseases caused by the bacteria.